Pediatric Low-Grade ACL Sprains: Trends in Characteristics, Management, and Outcomes. Issue 5 (31st May 2022) - Smith, Caitlyn; Worrall, Hannah; Ellis, Henry B.; Wilson, Philip L.; Jones, Jacob C.
Background: Anterior cruciate ligament (ACL) injuries are among the most common knee injuries in pediatric athletes. While much of the literature focuses on partial or complete tear of the ligament, there is little information on low-grade ACL sprains in either the adult or pediatric literature. Purpose: This study seeks to provide an analysis of grade 1 pediatric ACL sprains investigating injury characteristics, and report trends in management and outcomes. Methods: A retrospective review of patients, aged 8-19 years, presenting to a sports medicine clinic with a knee injury between January 2014-February 2021 was performed. Electronic medical records were queried for a diagnosis of low-grade ACL sprain based on radiology (MRI) reports that identified the injury. Charts were reviewed to collect data on demographics, sport history, injury details, clinical exam, return to play (RTP), and MRI findings. Descriptive statistics and comparisons within gender, age, and RTP were analyzed. Results: 67 patients were diagnosed with a grade 1 ACL sprain based upon clinical assessment and MRI findings and treated for such. Average age at injury was 14.51±2.46 years (56.72% male), with a mean RTP of 8.77±6.67 weeks from date of diagnosis and 12.57± 8.04 weeks from date of injury. Most frequent activities when injured were soccer (23.88%), football (16.42%), and basketball (14.93%).0 patients underwent ACL surgical treatment; 2 patients underwent surgery for concomitant injuries (both meniscus tears). 55 patients (82.09%) sustained one or more concomitant injuries: bone contusion (50.91%), non-ACL ligamentous injury (30.91%), meniscus injury (25.45%), soft tissue/muscular injury (12.73%), other (31.48%). 23 patients (37.7%) had non-negative Lachman on clinical exam. Successful conservative interventions included therapy (95.45%), bracing (87.88%), and activity restrictions (86.15%). Females were more likely to be injured in their primary sport than males (82.14% vs. 59.46%, p=0.05). Analysis of bone contusion location vs. RTP clearance date was performed. Patients who took longer to RTP (16+ vs <16 weeks) were more likely to also have a lateral femoral condylar (LFC) contusion (75% vs. 16.67%, p=0.05). Conclusion: Given limited literature on the topic, this review provides presentation characteristics and initial RTP correlates for pediatric low-grade ACL sprains. While longer term follow-up is needed as we continue to learn about the injury, the success rate of conservative treatment indicates that therapy, bracing, and activity restrictions may be considered over surgical management for low-grade ACL sprains.